HOW DO CURRENT MSMEs COFFEE SHOP PROMOTION STRATEGIES USE SOCIAL MEDIA? - Muh. Husriadi; Usman. M; Citra Ayu Ningsi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Growth Rapidly growing MSMEs coffee shops in Indonesia present new challenges in business competition, especially related to the use of social media as a tool effective promotion. This study aims to analyze the promotional strategies used by contemporary coffee shop MSMEs. through social media and identify factors that influence its effectiveness. The research method used is qualitative descriptive, with data collection through observation, interview in-depth, and documentation on several MSMEs coffee shops that are active on social media. The results of the study showed that the most effective promotional strategy involves the use of engaging visual content, collaboration with influencers, as well as interaction active with customers through social media features. This strategy has proven to be increase brand awareness, engagement customers, and sales. The implications of this research confirm the importance of innovation and digital adaptation for coffee shop SMEs to strengthen their position in a competitive market, as well as providing references practical and theoretical for business actors and academics in developing promotional strategies social media based.